Nas entrelinhas da história, memória e gênero. Lembranças da Fazenda Jatahy. - Andriolli, Carmen Silvia (2006)
This study presents the remembrances of female and male coffee-farm workers from the Jatahy Farm, located at the Luiz Antonio County, Northeastern region of the São Paulo State, Brazil. The Jatahy Farm was a property that along the 20th century had been through several manners of seizure; from 1925 to 1959 the farm was bought by the Companhia Mogiana de Estradas de Ferro, that extinguished the coffee plantation and in its place had started the pines and eucalyptus cultivation. In 1959 the Jatahy Farm had became a São Paulo State property and most of its area was turned into an experimental station focused on its local forest studies, resulting nowadays on an ecological station in which scientific researches and assisted environmental education are the only activities allowed. Although, thanks the seizure changes coffee farm to railway company property and then to a conservation area the working offers decreased and the Jatahy Farm s residents established out there since the time of coffee cultivation, soon by soon started leaving the place they used to live in. However, the multiplicity of meanings applied to the Jatahy Farm at the present, resulting from the effort on its conservation, are centered most on the sociability experienced in the past, when Jatahy Farm was a coffee farm. From that point on, this study is due to rebuild the collective memory of female and male Jatahy Farm s coffee workers, understanding Work in its multiple dimensions the work experienced in public and private circles as an analytical category, as way as Memory, Gender and, specifically, the Patriarchy concept. Consequently, this dissertation aims to discuss the gender differences existing on female and male memories, also considering the tenant farmers experiences as Italian immigrants. Reconstructing their life experiences throughout the Work as an analytical category is faced here as the ground zero for understanding sociabilities, representations and the multiplicity of meanings conferred to individual and collective life. Furthermore, the Gender category allows taking work, history and female opposed-power out off the invisibility, exploring the Patriarchy constructing and reconstructing process throughout time and, for that reason, its a-historical character. The time cut selected (1925-1959) is intended to include the periods in which Jatahy Farm was both a coffee farm and a Companhia Mogiana Railway property. The adopted research method was Oral History, by the possibilities it offers on registering and understanding remembrances, combined to other kinds of documents. The dialogue established amongst the variety of sources, oral and written, enhanced the relations on memory and history, which was focused on the local and regional historiography. The reconstruction of tenant farmers collective memory was also possible thanks to photographic sources, understood as a support for memories and the elaboration of affective maps by the deponents.